Recursos didácticos para corte y confección de la ropa deportiva y su incidencia en el proceso de enseñanza en la Sociedad de Artesanos del cantón La Mana provincia de Cotopaxi 2017 - Mejía Condo, Ana Esther (2017)
The objective of this research work is to determine the incidence of didactic resources for cutting and sewing and its impact on the process of teaching the production of sportswear in the society of artisans of the canton of Cotopaxi province "2017. In order to comply with the specific objectives, a population of 41 members was considered as the total of the universe as a sample, because the population is very small, in the same way an interview with the president. The analysis and interpretation of the tabulation of the surveys was carried out, which allowed reaching the general and specific conclusions, as a general conclusion it gives the opportunity to propose recommendations so that the educational problems found can be solved. It is recommended as a proposal the design of a guide of didactic resources of cut and confection suitable to promote the elaboration the sports clothes of quality in the society of craftsmen of the corner La Mana, province Cotopaxi in the year 2017